Employees in the health care management transformation - Teodorović Nevenka; Gajić-Stevanović Milena (Serbian Medical Society - Dental Section, Belgrade, 2008)
Introduction: The importance of studying management in one of the most sensitive and complex areas of human endeavor that is healthcare is of great significance for providing high quality and efficient easily-accessible healthcare in the future. Studying the challenges that need to be overcome towards achieving this goal is of great importance not only from the viewpoint of scientific management theory but primarily to help bring about strategically important decisions that are crucial for the continued evolution and reformation of the healthcare system, in which the employees have a new, much more complex role. The objective: was to more thoroughly study, describe and understand the role the employees have in the transformation of health care management. Material and method: During this research the material used was foreign and local literature, processed using the Analytical method as well as the Observation and Comparative methods. Conclusion: In the transformation of the health care management a very important role is played by the health care employees. Without the transformation of the current practice and significant changes in both the structure and work ethic of all the employees in health care services (nurses and people in management alike) there will be no improvement in the health care system overall.